Association of Vitamin D Deficiency with Ischemic Cardiomyopathy (Medical Forum Monthly, 2020)
Objective: The basic aim of this study is to analyze the association of vitamin D deficiency with ischemic cardiomyopathy.Study Design: Cross-Sectional studyPlace and Duration of Study: This study was conducted at the Government Khawaja Muhammad Safdar Medical College Sialkot during June 2019 till December 2019.Materials and Methods: All study participants underwent physical examinations, blood analysis, and echocardiographic evaluation. Venous blood samples were collected in the first part of the day after a short-term quick (10 to 12 hours). Afterwards, the serum was separated through centrifugation and immediately transported to the research facility for biochemical investigation.Results: The data was collected from 50 patients. There were no differences in age, gender, body mass index, and sun exposure within the groups. Biochemical parameters were not significantly different in all study participants except that patients with ICMP had low calcium levels than the control group. The mean 25(OH) D3 levels were significantly lower and NT-proBNP levels were significantly greater in patients with ICMP than controls.Conclusion: It is concluded that patients with ICMP had lower Vitamin D levels than controls, and Vitamin D deficiency had a significant relationship with cardiac function.